Pengaruh Audit Tenure dan Ukuran Perusahaan Terhadap Kualitas Audit: (Studi Kasus Pada Perusahaan Pertambangan Yang Terdaftar di BEI Periode Tahun 2019 - 2023) - Himawan, Irfan Sophan; Risa, Risa (Jurnal Ilmu Manajemen Retail Universitas Muhammadiyah Sukabumi, 2025)
This study aims to examine the effect of Audit Tenure and Company Size on Audit Quality. This research uses associative methods with a quantitative approach. The object of this research is, all types of mining companies listed on the IDX for the period 2019 - 2023, this study uses logistic regression analysis and data collection techniques, namely, purposive sampling, so that the sample in this study is 26 companies from a population of 79 companies, the data is obtained from secondary sources, namely, the company's annual financial statements which can be downloaded on the Indonesia Stock Exchange website, besides that secondary data sources are also obtained from literacy related to research topics. The results showed that audit tenure has a positive effect and a low level of significance on audit quality as indicated by a sig value of 0.429> 0.05, company size has a negative and significant effect on audit quality as indicated by a sig value of 0.016> 0.05, and audit tenure and company size have a significant effect on audit quality as indicated by a sig value of 0.005> 0.05.